Investigation of photophysicochemical properties of non-peripherally tetra-substituted metal-free, Mg(II), Zn(II) and In(III)CI phthalocyanines - Gorduk, Semih (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In the present work, the synthesis, characterization, photophysicochemical and aggregation properties of non-peripherally tetra-substituted metal-free (H2Pc), Mg(II) (MgPc), Zn(II) (ZnPc), and In(III)CI (InCIPc) phthalocyanines containing tetra (2,3-dihydro-1,4-benzodioxin-2-ylmethoxy) moieties were reported. The spectroscopic techniques were applied to characterize these phthalocyanines. The synthesized phthalocyanines exhibit very good solubility in many common solvents and their aggregation behaviors were examined using DMSO at different concentrations. The photophysicochemical (Fluorescence spectra, fluorescence, singlet oxygen and photodegradation quantum yield) properties were investigated in DMSO to detect the usability of the mentioned phthalocyanines as photosensitizers. Besides, the effects of the absence and presence of metal ion on their photophysicochemical properties are also researched. The metallo phthalocyanines (Mg, Zn and In) generated higher singlet oxygen than metal-free phthalocyanine derivative. According to singlet oxygen efficiency, the presence of metal ion on phthalocyanine ring increases singlet oxygen production. The results show that these phthalocyanines may be suitable candidates as photosensitizers in photodynamic therapy. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Photophysicochemical; Photodynamic therapy; Singlet oxygen; Metal ion; PHOTODYNAMIC ANTIMICROBIAL CHEMOTHERAPY; PHOTOCHEMICAL PROPERTIES; ZINC(II); PHOTOSENSITIZERS; THERAPY; BEHAVIOR; SOLVENT; Chemistry; Crystallography